Familiarity breeds contempt? Knowledge and understanding of democracy, support for democratization, and global city residence in Russia. Issue 3 (3rd April 2018) - Gerber, Theodore P.; Chapman, Hannah S.
ABSTRACT: Using Russian survey data from 2011 to 2012, this article examines public understanding of and support for democratization in a semi-authoritarian context. When knowledge of democracy is weak, and conceptual understanding of democracy is mixed—as in Russia—traditional measures of democratic support inadequately capture demand for democratization; that is, for more democracy than currently perceived. Contrary to conventional wisdom, Russians who adhere to "textbook" political definitions of democracy are more, not less, likely to advocate democratization. Residence in global cities increases support for democracy and democratization, while education fosters the latter but not the former. Other traditional indicators of middle-class status, such as income and urbanization, lack consistent effects. Based on these results we re-evaluate the mechanism linking modernization and support for democracy in developing, non-democratic societies. Rather than exert social-psychological or normative effects, modernization works primarily by raising exposure to global political discourses that define and promote democratic government.